Microbial functional diversity indicators in vineyard soils under organic and biodynamic land management - Tábata A. Bublitz; Heberto Rodas-Gaitan; Rainer Georg Joergensen; Vincent Masson; Juergen Fritz (Chemical and Biological Technologies in Agriculture)
Abstract Background An on-vineyard approach was used to investigate the effects of biodynamic (BD) preparations on microbial functional diversity and extracellular polymeric substances (EPS) in four vineyards on different bedrocks under organic management. Methods Soil organic carbon (SOC), total N, microbial biomass carbon (MBC), multi-substrate-induced respiration (MSIR), with 17 substrates and H2O, EPS, and glomalin-related soil protein (GRSP) were measured in soils taken from vineyards without (BD -) and with (BD +) biodynamic preparations. Results All parameters showed a significant vineyard effect due to specific soil types, and all, except GRSP and the GRSP/EPS-prot, showed an effect of BD preparations. BD + resulted in significant increases in MBC, MBC/SOC, EPS-carbohydrates and respiratory response for most vineyards but a significant decrease in the qCO2 values. The significant increases in mean SOC, Total N, CO2C, and the ratios EPS-carb/EPS-prot with BD +, as well as decreases in mean EPS-proteins and the ratios EPS-carb/MBC and EPS-prot/MBC were not reflected by significant differences between the individual vineyards. GRSP was negatively related to the microbial respiratory response of all substrates added. Conclusions The significant effects of vineyard are closely connected to soil pH and texture. The significant increases in BD +, visible in MBC, MBC/SOC and EPS-carbohydrates, and the latter positive correlation with the respiratory response demonstrates an improvement of soil chemical and biological properties for most vineyards. Lower ratios of EPS-carb/MBC, EPS-prot/MBC and amounts of EPS-protein indicate that soil microorganisms diverted less substrate to the formation of EPS and more to the production of microbial biomass. GRSP and GRSP/EPS-prot did not show any explainable pattern. Future investigations on soil structure might be of benefit for studies on the effect of BD preparations in vineyards. Graphical Abstract